A Novel Homozygous Missense Mutation in the Zinc Finger DNA Binding Domain of GLI1 Causes Recessive Post-Axial Polydactyly - Umair, Muhammad; Ahmad, Farooq; Ahmad, Saeed; Alam, Qamre; Rehan, Mohd; Alqosaibi, Amany I.; Alnamshan, Mashael M.; Rafeeq, Misbahuddin M; Haque, Shahnaz; Sain, Ziaullah M; Ismail, Muhammad; Alfadhel, Majid (Frontiers in Genetics, 2021)
Background: Polydactyly is a very common digit abnormality, characterized by having extra digits/toes. Non-syndromic form of polydactyly is caused due to pathogenic mutations in eleven genes GLI3, GLI1, ZRS regulating LMBR1, IQCE, ZNF141, PITX1, MIPOL1, FAM92A, STKLD1, KIAA0825, and DACH1. Method: To identify the culprit gene, a single affected family member (IV-4) was subject to whole-exome sequencing (WES). Bi-directional Sanger sequencing was performed to segregate the identified variant within the family. Insilco analysis was performed to investigate the effect of the variant on DNA binding properties. Results: WES identified a bi-allelic missense variant (c.1010C>T; p.Ser337Leu) in exon 9 of the GLI1 gene located on chromosome 12q13.3. Using Sanger sequencing, the identified variant segregated perfectly with the disease phenotype. Insilco analysis of this DNA binding protein revealed that the variant weakened the DNA binding interaction, which might result in indecorous GLI1 function. Conclusion: Herein, we report a novel variant in the GLI1 gene, causing autosomal recessive PAPA type 8. This confirms the important role of GLI1 in digit development and might help in genotype-phenotype correlation in the future.